THE eval_UATION OF PRESCRIPTION SCREENING PHASE PRESCRIBING ERROR IN PEDIATRIC PRESCRIPTIONS AT MITRAKITA CLINIC SEMARANG PERIOD JANUARY 2024 - Damayanti, Widiya Widiya (Jurnal Penelitian Farmasi Dan Herbal, 2025)
The issue of Medication Error in prescriptions can cause harm to patients that may result in a mistake in the use of drugs. Incomplete prescriptions, whether administratively, pharmaceutically, or clinically, can lead to medication errors. This study was conducted to eval_uate the completeness of prescriptions in the administrative, pharmaceutical, and clinical aspects of pediatric prescriptions at the Mitrakita Clinic and to ascertain compliance with Minister of Health Regulation No. 34 of 2021. This research is an observational study that is descriptive in nature, using a retrospective data collection method on pediatric prescriptions at the Mitrakita Clinic for the month of January 2024. Data collection in this research employed random sampling with a sample size of 160 prescriptions. Prescriptions were eval_uated for their compliance administratively, pharmaceutically, and clinically based on Minister of Health Regulation No. 34 of 2021. The data obtained was processed using SPSS with univariate analysis methods (descriptive analysis) and presented in the form of tables and percentages. This study aims to reduce the risk of medication errors in prescriptions at Mitrakita Clinic Semarang. Data from 160 prescriptions, after being tested and analyzed using SPSS, showed that the data were normally distributed and homogeneous. The results of the prescription screening eval_uation for prescribing errors in pediatric prescriptions at Mitrakita Clinic Semarang showed that the percentage of errors in the administrative review was 29.922%, in the pharmaceutical review was 5.104%, and in the clinical review was 14.018%. Thus, the average medication error occurring in pediatric prescriptions at Mitrakita Clinic during January 2024 was 16.348%, leading to the conclusion that prescriptions made at Mitrakita Clinic Semarang are in accordance with Minister of Health Regulation No. 34 of 2021.